SOCIAL TRANSFORMATION IN THE DIGITAL AGE: ANTHROPOLOGICAL PERSPECTIVES ON TECHNOLOGY AND CULTURAL CHANGE - Indra Tjahyadi; Carlos Fernandez; Isabel Martinez; Emmy Solina (Cognitionis Civitatis et Politicae, 2026)
Digital technologies have profoundly reshaped contemporary social life, altering patterns of interaction, identity formation, and cultural transmission across societies. From an anthropological perspective, these transformations cannot be understood solely through technical or economic explanations, but require attention to meaning, practice, and power embedded in everyday digital engagement. This study aims to analyze social transformation in the digital age by examining how technology functions as a culturally embedded social environment that mediates relationships, values, and symbolic expression. The research employs a qualitative design grounded in interpretive anthropology, combining digital ethnography, semi structured interviews, and analysis of online cultural artifacts to capture lived experiences within hybrid online offline spaces. The findings reveal that digital platforms reconfigure social organization, redistribute cultural authority, and intensify reflexive identity practices while simultaneously sustaining elements of cultural continuity. Digital interaction emerges as a site of negotiation where tradition and innovation intersect rather than as a force of unilateral disruption. The study concludes that social transformation in the digital age is best understood as a dynamic and context dependent process shaped by human agency and cultural interpretation. These results highlight the continued relevance of anthropological approaches for interpreting technological change and offer insights for research on digital society.